Edge-dislocation-induced ultrahigh elevated-temperature strength of HfMoNbTaW refractory high-entropy alloys - Ko-Kai Tseng; Hao-Hsuan Huang; Woei-Ren Wang; Jien-Wei Yeh; Che-Wei Tsai (Science and Technology of Advanced Materials)
Over 150 refractory high-entropy alloys (RHEAs) have been proposed in the last decade. Early alloys such as MoNbTaW and MoNbTaVW still show an unparalleled yield strength of approximately 400 MPa at 1600°C. However, RHEAs with even elevated high-temperature strength are necessary in aerospace vehicles and nuclear reactors to cope with advanced technology in the future. Here, solid-solution strengthening calculation and melting point prediction are combined to design single-phase RHEA for attaining ultrahigh strength at 1600°C. The results show that Hf0.5MoNbTaW and HfMoNbTaW alloys after fully homogeneous treatment at 2100°C for 2 h reveal a homogenous body-centered cubic phase. HfMoNbTaW alloy exhibits a yield strength of 571 MPa at 1600°C, much higher than that of MoNbTaVW (477 MPa). It is found that a plateau of strength occurs from 800°C to 1200°C, which is important for raising the strength level of RHEAs at high temperatures. This strengthening mechanism is explained with the change of deformation mode from screw to edge dislocations, which contributes an edge-dislocation-induced strength. A similar alloy design strategy could be applied to develop more RHEAs with an ultrahigh strength level.